Demographic and clinical characteristics of gastric cancer patients in north of Iran, Mazandaran province, 2008-2014 - Seyed Khalil Mousavi; Ghasem Janbabai; Bizhan Kouchaki; Hanieh Borhani; Masoumeh Rashidi; Ebrahim Salehifar (Mazandaran University of Medical Sciences, 2015)
Gastric cancer has been known as a poor prognosis disease with a high degree of mortality. In Iran, it has been increased during the previous two decades, especially in northern part of the country. The aim of this study was to determine the demographic and clinical characteristics of gastric cancer in Mazandaran province. All patients with gastric cancer diagnosis treated in the Imam Khomeini educational hospital or Touba Polyclinic, a university affiliated center, from March 2008 to March 2014 were included. Demographic data, the symptoms at the time of presentation, tumor size, type of tumor, lymph node involvement, status in terms of metastatic disease, therapeutic plan and type of chemotherapy regimens were gathered from patients’ medical records. Statistical analysis was performed using SPSS, version 16. Totally, 643 patients were investigated. The mean age of patients was 64.34 years and men were more affected than women. “Time to relapse” and “time to progression” were 13 and 6.5 months, respectively. The most common initial symptoms at diagnosis were nausea, vomiting and epigastric pain (47.4%). Only in 6.3%, the disease was diagnosed at the initial stages. The most common site of involvement was cardia (almost 40%) and antrum (32%). More than 91% of tumors were adenocarcinoma. DCF (Docetaxel, Cisplatin, 5FU) (43.3%), Xeloda (15.2%), DOX (Docetaxel, Oxaliplatin) (13.8%) and ECF (Epirubicin, Cisplatin.5FU) (9.2%) were the most common used regimens. There was a trend for improved survival with DCF regimen (P = 0.08). Most gastric cancer patients were referred in the advanced stage or metastatic disease. The demographic characteristics are consistent with other previous reports. DCF regimen may have some advantages over other chemotherapy regimens.